Nature-based solutions for climate change adaptation: A systematic review of systematic reviews - Johnson, Brian Alan; Kumar, Pankaj; Okano, Naoyuki; Dasgupta, Rajarshi; Shivakoti, Binaya Raj (Nature-based solutions, 2022)
•We reviewed the prior systematic reviews related to nature-based solutions for climate change adaptation (NBS-CCA) and analyzed their general characteristics, including their geographic scopes, research objectives, and literature sources used for analysis.•Most reviews focused on adaptation benefits/trade-offs of NBS in urban and coastal areas, while many NBS are actually implemented in forest/rural areas. This disparity suggests research is less focused on the direct benefits of NBS to forest/rural areas, and more on how forest/rural NBS indirectly benefit more human-modified areas.•While many prior reviews have focused on the outcomes of NBS (e.g. adaptation benefits/trade-offs) and policy/governance issues, few have focused specifically on social issues. It may be a priority for future systematic reviews as well as primary studies on NBS-CCA. More than 90 systematic reviews have been conducted on the topic of nature-based solutions for climate change adaptation (NBS-CCA). These prior reviews, however, are scattered across more than 45 different peer-reviewed journals and gray literature sources, making it difficult to follow all of the knowledge generated and remaining research gaps. In this study, we conducted a systematic review of systematic reviews on the topic of NBS-CCA, with the objective of mapping and analyzing these prior reviews. We found that most of the prior systematic reviews had relatively narrow research focuses, typically focusing on a particular geographic context of NBS-CCA (mainly in urban and coastal areas) or on a particular aspect of NBS-CCA planning/implementation (mainly outcomes assessment and policy/governance issues). Fewer reviews focused on mountainous areas or on social and financial aspects of NBS-CCA planning/implementation. The majority reviews relied solely on peer-reviewed literature for analysis, with only 26% including gray literature, despite the large amount and variety of gray literature on NBS-CCA that exists. Notably, we found that no prior systematic reviews have yet attempted to comprehensively analyze all geographic contexts and all aspects of NBS-CCA, e.g. through a review and meta-analysis of all available peer-reviewed and gray literature on the topic. This would likely require a massive multidisciplinary effort, but could be a worthy endeavor considering the realized need to integrate NBS-CCA into national/subnational policies and various international environmental agreements pertaining to climate change (e.g., Paris Agreement) and biodiversity conservation (e.g., Post-2020 Global Biodiversity Framework).